Belajar dari Kerukunan Antar Umat Beragama di Kalimantan Timur dan Implikasinya terhadap Pendidikan Karakter: (Perspektif Psikologi Lintas Agama dan Budaya) - Nur Kholik Afandi (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2018)
East Kalimantan is one of the provinces in Indonesia which has a high diversity of levels, both from the aspect of tribes, cultures, and religions. Special for its diversity in community life religiosity in Kaltim, sure to be a challenge for the Government to manage the differences so as not to cause conflict between believers. One of the agencies that have a role in keeping and choose between religious harmony is the harmony between Religious Forum in Kaltim (FKUB), both in the district/city level landscape or province. Keharmorisan the relationship between religious, cannot be separated from the central role played and religious figures as well as community leaders who are members of the stewardship FKUB. The phenomenon of religious harmony which exists in Kaltim can serve as a model to instil the values of multicultural and multi-religious, based on the growing awareness of the values of the differences existing in the community. Characters that need to be built in creating a harmonious religious life religious character that is put forward on the cultivation of the religious beliefs values and awareness about the existence of differences in religion, keeping each other honour, respect and tolerance.